Evaluation of psycho-emotional state of dentists in conducting outpatient dental procedures (Эндодонтия Today)
It is believed that dental treatment, patients may be the cause of acute and chronic stress, especially in the absence of adequate anesthesia. The aim of the work was to assess the degree of emotional stress at the dentists during local anesthesia at the dentist general practice of using the Maslach questionnaire 60 physicians aged 25-55 years. It has been shown that stressful situation related to the prediction of the effectiveness of local anesthesia and its security, may underlie the formation of burnout syndrome